Augmented Quadruple-Phase Contrast Media Administration and Triphasic Scan Protocol Increases Image Quality at Reduced Radiation Dose During Computed Tomography Urography. Issue 2 (March 2018) - Saade, Charbel; Mohamad, May; Kerek, Racha; Hamieh, Nadine; Alsheikh Deeb, Ibrahim; El-Achkar, Bassam; Tamim, Hani; Abdul Razzak, Farah; Haddad, Maurice; Abi-Ghanem, Alain S.; El-Merhi, Fadi
Abstract : Purpose: The aim of this article was to investigate the opacification of the renal vasculature and the urogenital system during computed tomography urography by using a quadruple-phase contrast media in a triphasic scan protocol. Materials and Methods: A total of 200 patients with possible urinary tract abnormalities were equally divided between 2 protocols. Protocol A used the conventional single bolus and quadruple-phase scan protocol (pre, arterial, venous, and delayed), retrospectively. Protocol B included a quadruple-phase contrast media injection with a triphasic scan protocol (pre, arterial and combined venous, and delayed), prospectively. Each protocol used 100 mL contrast and saline at a flow rate of 4.5 mL. Attenuation profiles and contrast-to-noise ratio of the renal arteries, veins, and urogenital tract were measured. Effective radiation dose calculation, data analysis by independent sample t test, receiver operating characteristic, and visual grading characteristic analyses were performed. Results: In arterial circulation, only the inferior interlobular arteries in both protocols showed a statistical significance ( P < 0.05). Venously, the inferior vena cava, proximal and distal renal veins demonstrated a significant opacification reduction in protocol B than in protocol A ( P < 0.001). Protocol B showed a significantly higher mean contrast-to-noise ratio than protocol A (protocol B: 22.68 ± 13.72; protocol A: 14.75 ± 5.76; P < 0.001). Radiation dose was significantly reduced in protocol B (7.38 ± 2.22 mSv) than in protocol A (12.28 ± 2.72 mSv) ( P < 0.001). Visual grading characteristic ( P < 0.027) and receiver operating characteristic ( P < 0.0001) analyses demonstrated a significant preference for protocol B. Conclusions: In computed tomography urography, augmented quadruple-phase contrast media and triphasic scan protocol usage increases the image quality at a reduced radiation dose.